Iridium, carbon and nitrogen multiple-doped TiO2 Nanoparticles with enhanced photocatalytic activity. Issue 5 (1st April 2017) - Zhao, X.G.; Huang, L.Q.
Abstract: The aim of this research is to enhance the photocatalytic activity of TiO2 nanoparticles for the UV–visible light by multiple-doping with Iridium, carbon and nitrogen. The tridoped TiO2 photocatalyst were prepared by wet chemical method, and characterized by X-ray diffraction, Raman spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, ultraviolet-visible light diffuse reflection spectroscopy and room temperature photoluminescence spectroscopy. Besides, the photocatalytic H2 evolution performance of Ir-C-N tridoped TiO2 under UV–visible light irradiation was evaluated. It was found that Ir existed as Ir 4+ by substituting Ti in the lattice of TiO2 ; meanwhile, C and N were also incorporated into the surface of TiO2 nanoparticles in interstitial mode. Meanwhile, Ir-C-N tridoping extended the absorption of TiO2 into the visible light region and narrowed its band gap to 3.0 eV, resulting in enhanced photocatalytic H2 evolution under UV–visible light irradiation. This could be attributed to narrow band gap and proper electronic structure of TiO2 after Ir-C-N tridoping.